The effect of the electronic transmission of prescriptions on dispensing errors and prescription enhancements made in English community pharmacies: a naturalistic stepped wedge study - Franklin, Bryony Dean; Reynolds, Matthew; Sadler, Stacey; Hibberd, Ralph; Avery, Anthony J.; Armstrong, Sarah J.; Mehta, Rajnikant; Boyd, Matthew J.; Barber, Nick (BMJ Publishing Group, 2014)
Objectives: To compare prevalence and types of dispensing errors and pharmacists’ labelling enhancements, for prescriptions transmitted electronically versus paper prescriptions. Design: Naturalistic stepped wedge study. Setting: 15 English community pharmacies. Intervention: Electronic transmission of prescriptions between prescriber and pharmacy. Main outcome measures: Prevalence of labelling errors, content errors and labelling enhancements (beneficial additions to the instructions), as identified by researchers visiting each pharmacy. Results: Overall, we identified labelling errors in 5.4% of 16 357 dispensed items, and content errors in 1.4%; enhancements were made for 13.6%. Pharmacists also edited the label for a further 21.9% of electronically transmitted items. Electronically transmitted prescriptions had a higher prevalence of labelling errors (7.4% of 3733 items) than other prescriptions (4.8% of 12 624); OR 1.46 (95% CI 1.21 to 1.76). There was no difference for content errors or enhancements. The increase in labelling errors was mainly accounted for by errors (mainly at one pharmacy) involving omission of the indication, where specified by the prescriber, from the label. A sensitivity analysis in which these cases (n=158) were not considered errors revealed no remaining difference between prescription types. Conclusions: We identified a higher prevalence of labelling errors for items transmitted electronically, but this was predominantly accounted for by local practice in a single pharmacy, independent of prescription type. Community pharmacists made labelling enhancements to about one in seven dispensed items, whether electronically transmitted or not. Community pharmacists, prescribers, professional bodies and software providers should work together to agree how items should be dispensed and labelled to best reap the benefits of electronically transmitted prescriptions. Community pharmacists need to ensure their computer systems are promptly updated to help reduce errors.